Kemampuan Literasi Matematika Peserta Didik dalam Menyelesaikan Soal PISA Konten Space and Shape Ditinjau dari Gaya Kognitif - Ani Safitri; Rita Pramujiyanti Khotimah (Jambura Journal of Mathematics Education, 2023)
Students need to have mathematical literacy skills because it can help in making the right decisions and understanding the application or role of mathematics in real life.  The results of the PISA survey, in Indonesia, the ability of mathematical literacy shows that it is still not optimal and similar incidents continue to occur, indicating that mathematical literacy skills are still low. The purpose of this research is to analyze the mathematical literacy skills of students in solving PISA questions on space and shape content in terms of cognitive style. This research method uses a descriptive with qualitative approach.  The research subjects consisted of 2 students of class IX C of Muhammadiyah Junior High School in Surakarta. The instruments used were Group Embedded Figures Test (GEFT), mathematical literacy test, and interview guidelines. Data analysis used the Milles and Hubberman model, namely: data reduction and presentation, and conclusions. The results showed the ability of mathematical literacy in terms of cognitive style and concluded that FI learners can master all indicators of mathematical literacy in the three questions well. FD learners can master all indicators of mathematical literacy skills on questions number one and two whereas, on question number three FD learners have not mastered the indicators of reasoning and giving reasons because they are less careful in understanding the problems given.